ANALISIS FATTY ACID ETHYL ESTER DENGAN INFRA RED DALAM DARAH TIKUS WISTAR SETELAH MINUM ALKOHOL SECARA AKUT - Suaniti, Ni Made (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011, 2012)
Fatty acid ethyl esters (FAEE) are the result of biochemical reactions in the body after drinking alcohol acutely. In general, alcoholic drinks contain ethanol, which can be analyzed chemically as ethanol and its metabolites. Metabolite of ethanol are the result of ethanol oxidation reaction and the reaction of ethanol with endogenous compaounds in the body. One of the metabolites of ethanol is an ester compound resulted from the reation of ethanol with fatty acids. This study aims to prove the existence of FAEE functional group as one of biochemical markers in acute alcohol consumers. Two groups of wistar rats were given distilled water (control group) and 20% alcohol (treaed group) every day for 1 week. Biochemical markers analyzed are FAEE. This research was conducted in two phases: the first phase, is the treatment of rats with acute alcohol. The second phase, analysis of chemical compounds: FAEE with Infra Red Spectrophotometer. Wistar rat blood samples taken 6 and 24 hours after drinking alcohol acutely were analyzed qualitatively. Functional Groups indicating the presence of FAEE are C-H (3600-2500 cm-1), the ketone group (C = O) appears at 1870-1540 cm-1, stretching vibration of CO or C-C (= O)-O at 1190-1140 cm- 1.
Keywords: Fatty Acid Ethyl Esters, alcohol, Wistar rats, Infra Red